Effect of continuous and alternating episodes of starvation on behavior and reproduction in the red flour beetle. (25th March 2018) - Gilad, T.; Koren, R.; Moalem, Y.; Subach, A.; Scharf, I.
Abstract: Stress in general and starvation in particular have various and often contrasting effects on different traits. Previous starvation studies have usually focused on one or two response variables and comprised one starvation treatment versus a control. Here, we used the red flour beetle to study the effects of (1) a starvation gradient of 0–4 days, and (2) alternating starvation over 3 days on multiple response variables: movement activity, food patch discovery, latency to emerge from shelter, body mass, water content, and offspring number and mass. Starvation led to a decline in body mass and water content, as expected. Beetles also became less active, less explorative and less bold, which is in contradiction to the findings from some previous work. Both the number of offspring and their mass at mid‐development diminished, suggesting a non‐adaptive parental effect, from the offspring perspective, due to parental starvation. Recuperation episodes negated starvation effects in most cases, with three exceptions: male body mass, water content and movement activity. The link between starvation duration and the tested response variables was inconsistent between sexes, with movement activity the most prominent example. Females were generally larger and although the rate of their mass loss was steeper, they were more starvation tolerant than males, as evident in their ability to take better advantage of the recuperation episodes. Our results indicate that starvation has a differential effect on the response variables according to sex. Abstract : We used the red flour beetle to study the effects of (1) a starvation gradient of 0–4 days, and (2) alternating starvation over 3 days on multiple response variables. Starvation led to a decline in body mass and water content. Beetles became less active, less explorative and less bold. The number of offspring and their mass at mid‐development diminished due to parental starvation. Recuperation episodes negated starvation effects in most cases, with three exceptions: male body mass, water content and movement activity. The link between starvation duration and the tested response variables was inconsistent between sexes, with movement activity the most prominent example. Females were generally larger and although the rate of their mass loss was steeper, they were more starvation tolerant than males, as evident in their ability to take better advantage of the recuperation episodes. Illustration credit: Inon Scharf.